Pengaruh Budaya Organisasi Dan Lingkungan Kerja Terhadap Kinerja Pegawai Pada Puskesmas Dangung- Dangung Kabupaten Lima Puluh Kota - Maharani Wennisa Putri; Henryanto Abaharis (Maslahah : Jurnal Manajemen dan Ekonomi Syariah, 2023)
This study aims to examine the effect of organizational culture and work environment on employee performance at the Dangung-Dangung Health Center, Fifty Cities District. This type of research is quantitative, where the research process emphasizes objective measurement of results using statistical analysis. The population in this study were all employees of 73 people. The sample collection technique used is the total sampling technique, where total sampling is the sampling technique when all members of the population are sampled, while the number of samples is 73 people obtained from all members of the staff. The type of data used in this research is quantitative and qualitative data. While the data sources are primary and secondary data sources. Data collection techniques using observation, questionnaires and literature study. By using test instrument test, (validity test and reliability test), analysis descriptive test, classical assumption test (normality test, multicollinearity test and heteroscedasticity test) then multiple linear regression and hypothesis testing with the help of the SPSS application. The results of the study show that organizational culture has a positive and significant effect on employee performance and the work environment has a positive and significant effect on employee performance.